Sociodemographic factors associated with cyberchondria related to COVID-19 in medical students from two Peruvian universities - Revilla-Bravo, javier (2025)
Objectives: To examine the link between COVID-19-related cyberchondria and sociodemographic factors among medical students from two Peruvian universities. Methods: Cross-sectional observational study conducted in 345 students from two Peruvian medical schools (2020–2021) using an online questionnaire. Results: Significant differences were found by age, as cyberchondria levels decreased with increasing age. Students with family members working in health had lower scores on the “excessive” subscale. No association was found between cyberchondria and gender, marital status, or having a relative diagnosed with COVID-19. Conclusions: Cyberchondria was inversely associated with age; older participants had lower levels. Having relatives in the health field was associated with lower cyberchondria, while gender, marital status, and relatives with COVID-19 showed no relationship.